Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae) - Kottelat, Maurice (Zootaxa, 2017)
Schistura epixenos, new species, is described from the Nakai Plateau in Laos. It is distinguished from its congeners in Southeast Asia with a pattern of dark brown bars on a pale brown background by a combination of characters including, among others, a slender body, body with 13–17 bars reaching downwards to the level of the pectoral fin, a complete lateral line, scales present in the predorsal area, and the pelvic-fin origin below the dorsal-fin origin.